PP12 Interventions to Promote Healthy Eating: A Systematic Review Of Regulatory Approaches. (10th September 2013) - Hendry, V; Monsivais, P; Almiron-Roig, E; Jebb, S; Neelon, S Benjamin; Griffin, S; Ogilvie, D
Abstract : Background: Unhealthy diets are a risk factor for many chronic diseases, accounting for around 40% excess cardiovascular and cancer mortality annually across the United Kingdom. Multifactorial strategies may help address this, and governments employ a variety of approaches to influence individual diets, the prevalence of obesity and population health. This systematic scoping review considers the effectiveness of regulatory interventions to change diet or diet-related behaviour. Methods: The review includes regulation, rules and legislation (collectively, "regulation") seeking to directly alter diet, dietary behaviour or nutrition by influencing (a) dietary behaviour (e.g. through regulating labelling, calorie display, marketing, food in schools, or built environments; or by using taxes or subsidies) or (b) the nutritional content of food (e.g. by specifying salt or trans fat levels). The review follows Cochrane and EPPI-Centre guidance and comprises a scoping review of regulatory interventions, and in-depth reviews on (1) school-based fruit and vegetable schemes and (2) control of trans fats. Medline, Embase, ISI WoK, EconLit, grey literature and bibliographic searches to the end of December 2012 identified 134 studies eligible for full text review. Studies were included if they had a recognisable research design. Results: Studies of information labels (packaging or menus) and compliance with school food standards occurred most frequently. Six studies of school-based fruit and vegetable schemes provided moderate evidence of short-term increases in intake but weak evidence for any longer term behaviour changes. Thirteen studies examined trans fat controls through bans or labelling. These measures achieved good compliance if regulation was monitored, with evidence of food reformulation following both bans and labelling. Removing trans fats had minor effects on food availability, price or quality, although some 'trans free' foods commanded a price premium. The costs of removing trans fats were not reported. Conclusion: Regulations with monitoring achieved compliance, but whether this affects food choices, dietary behaviour, nutrition, obesity prevalence or other health outcomes is unclear since those impacts have been under-evaluated. Regulation to influence dietary behaviour as well as the nutritional content of food can be used as a structural intervention to help create healthier living environments. Mandated labelling may risk exacerbating inequalities unless individual behaviour is also considered, and could be used to mislead consumers by providing a 'healthy halo' for unhealthy food. Understanding the effectiveness and costs of regulatory interventions will highlight where government-led action may be effective in promoting healthy diets in the population.